PAKOM PETERNAK PUYUH DESA GAJAHAN COLOMADU KARANGANYAR - Hakim, Lukman; Hanwar, Dedi; Sugiyanto, Eko; Irawati, Zulfa (WARTA, 2015)
The purpose of this activity is improving knowledge and skill of quail farmerâs in waste management of quail. The management of waste is processing of organic fertilizer. The participate in the activity are quail farmerâs in RW II Sub-village Ginung, Gajahan Village, Colomadu, Karanganyar. The result of this activity in step I that is be good attention from a quail farmerâs especiality at trainning time process of product organic fertilizer. As for its result as follows; trainning and assistence quail farmerâs is followed enthusiastic fully by participant and greeted positive by head of Village Gajahan Colomadu, Karanganyar. That are many question in trainning process of product organic fertilizer. The others result in activity is a quail farmerâs started processing of product organic fertilizer in housebreed themselves. TheÂ  processing of product organic fertilizer will be clean in Gajahan Village environment and also this activity will be value added toward income quail farmerâs.